Wind power integration into the automatic generation control of power systems with large‐scale wind power. Issue 10 (10th October 2014) - Basit, Abdul; Hansen, Anca Daniela; Altin, Mufit; Sørensen, Poul; Gamst, Mette
Abstract : Transmission system operators have an increased interest in the active participation of wind power plants (WPP) in the power balance control of power systems with large wind power penetration. The emphasis in this study is on the integration of WPPs into the automatic generation control (AGC) of the power system. The present paper proposes a coordinated control strategy for the AGC between combined heat and power plants (CHPs) and WPPs to enhance the security and the reliability of a power system operation in the case of a large wind power penetration. The proposed strategy, described and exemplified for the future Danish power system, takes the hour‐ahead regulating power plan for generation and power exchange with neighbouring power systems into account. The performance of the proposed strategy for coordinated secondary control is assessed and discussed by means of simulations for different possible future scenarios, when wind power production in the power system is high and conventional production from CHPs is at a minimum level. The investigation results of the proposed control strategy have shown that the WPPs can actively help the AGC, and reduce the real‐time power imbalance in the power system, by down regulating their production when CHPs are unable to provide the required response.